PELAKSANAAN TRADISI PASAMBAHAN MANJAPUIK MARAPULAI DI KANAGARIAN PANAMPUANG, KECAMATAN AMPEK ANGKEK, KABUPATEN AGAM, SUMATERA BARAT - Muhammad Ihsan.R; Jonyanis ' (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Oral literature in the Minangkabau language is known as the pasambahan manjapuik marapulai tradition. According to Minangkabau culture, this tradition is carried out at weddings. One type of reciprocal pasambahan is the pasambahan which is performed during the manjapuik marapulai event. Kanagarian Panampuang West Sumatra, Ampek Angkek District, Agam Regency became the location of this research. Determining the normative and empirical application of the pasambahan manjapuik marapulai tradition is the aim of this research. This study uses a qualitative descriptive research methodology. The purpose of qualitative descriptive research is to reveal facts, situations, and various phenomena that occur. Disclosure of the implementation of normative traditions associated with this inquiry. So, the writer will develop the concept and collect information related to the research subject. In-depth interviews and observations were used as data collection methods. While the qualitative descriptive data analysis method includes data collection, data reduction, data presentation, and making conclusions and suggestions. Based on the application of the study findings, there has been a shift from normative standards regarding roles, duties, and how they are carried out in the application of tradition. The pasambahan manjapuik marapulai tradition upholds moral principles which include humility, politeness, deliberation, thoroughness, and compliance with applicable customary law. Keywords: Manjapuik Marapulai Pasambahan Tradition, Normative Implementation, Empirical Implementation.